The Effect of Bank Recapitalization and Corporate Governance on Performance of Banking Sector: A Proposed Conceptual Framework - Umar Muhammed Dikko; Mohd Norfian Alifiah (International Journal of Economics and Financial Issues, 2019)
The global financial crisis of the last decade has been described as the most serious crisis that affects the world's economy since the Great Depression of 1940, which lead to the bank's recapitalization exercises in many countries. The purpose of this study is to propose a conceptual framework that will investigate the effect of bank recapitalization on the performance of the banking sector and to measure the moderating effect of corporate governance. However, the nature and existence of this relationship are found to be mixed and inconclusive (i.e., positive, negative, or no relationship at all). These have prompted scholars, experts, and authorities to re-examine the relationship between recapitalization and the performance of the banking sector. This study addresses the research deficit and proposes a conceptual and theoretical framework for measuring the effectiveness of bank recapitalization, corporate governance on the bank's performance, which could be used by banks and other regulatory bodies. Furthermore, a recommendation for future research in this area also suggested.